GAMING ADDICTION AND ACADEMIC PERFORMANCE: A BATTLE FOR STUDENT SUCCESS - Mohd Shukry , Amira Idayu; Zaidi, Nur Amirah Syahirah; Mat Nawi , Nur Ainatul Mardiah; Abdullah , Nurulannisa; Nik Rosli , Nik Nur Izzati; Idris , Zaila (Journal of Islamic, Social, Economics and Development, 2024)
This study investigates the relationship between gaming addiction and academic performance among students at Universiti Teknologi MARA (UiTM). With the rapid advancement of technology and the increasing accessibility of online gaming platforms, concerns regarding the impact of gaming on students' academic success have emerged. An online questionnaire was administered to gather data from 100 students, of which 68 responses were deemed suitable for analysis. The findings reveal a significant prevalence of gaming addiction among the respondents, with a notable correlation between excessive gaming and diminished academic performance. The study highlights the demographic characteristics of the participants, including gender, age, and educational level, which may influence the outcomes. The results underscore the need for awareness and intervention strategies to mitigate the adverse effects of gaming addiction on students' academic achievements.